Evaluation of the existing conditions of lasiana beach tourism destinations and ecosystems, Kupang City - Kore, Jefirstson Richset Riwu; Ora, Fellyanus Haba; Saubaki, Moniche Aletha; Kore, Herison Richset Riwu (CV. Austronesia Akademika, 2024)
This research aims to determine the existing conditions of the destination and ecosystem of Laisiana beach tourism and evaluate the performance and importance of these existing conditions. This research falls under the action research design with data acquisition techniques using interview, observation, and documentation techniques. Determining the research population is through non-probability sampling with a convenience sampling approach and key actors sampling. The number of research samples is 75 people. Variable measurement is done on a Likert scale. The data types consist of primary and secondary data. Data analysis is done using a quantitative approach, namely interval technique and IPA analysis. The research results indicate that there is still a gap between the existing conditions of the destination and the tourism ecosystem towards satisfaction. The evaluation results show that the existing conditions of tourist destinations have not been a focus while the expectations of tourists are very high. Unlike the existing tourism conditions, most attributes such as community acceptance, tourist locations, tourist products, investments, development policies, and supporting tourism industries are expectations of tourists to be improved but are not a priority, while aspects that are not of concern to tourists receive excessive attention such as tourist targets, supporting facilities, tourism trends, product value, marketing, and tourism resources.